2018
DOI: 10.1111/apha.13075
|View full text |Cite
|
Sign up to set email alerts
|

Trans‐life cycle acclimation to experimental ocean acidification affects gastric pH homeostasis and larval recruitment in the sea star Asterias rubens

Abstract: Parental pre-acclimation to acidification levels that are beyond the pH that is encountered by this population in its natural habitat (eg, pH 7.2) negatively affected larval size and development, potentially through reduced energy transfer. Maintenance of alkaline gastric pH and reductions in maternal energy reserves probably constitute the main factors for a reduced juvenile recruitment of this marine keystone species under simulated OA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 95 publications
2
13
0
Order By: Relevance
“…As noted earlier for copepods, trans-generational acclimation to OA has also been reported for benthic invertebrates (e.g. Dupont et al 2013 ; Hu et al 2018 ), and here too, prior environmental history appears to influence tolerance (Hu et al 2018 ). Dissecting the effects of trans-generational plasticity from other forms of plasticity is complex and more, targeted experimentation is required before generalisations can be made on the potential for trans-generational plasticity in benthic animals (Torda et al 2017 ).…”
Section: Direct Effects Of Ocean Acidificationsupporting
confidence: 83%
“…As noted earlier for copepods, trans-generational acclimation to OA has also been reported for benthic invertebrates (e.g. Dupont et al 2013 ; Hu et al 2018 ), and here too, prior environmental history appears to influence tolerance (Hu et al 2018 ). Dissecting the effects of trans-generational plasticity from other forms of plasticity is complex and more, targeted experimentation is required before generalisations can be made on the potential for trans-generational plasticity in benthic animals (Torda et al 2017 ).…”
Section: Direct Effects Of Ocean Acidificationsupporting
confidence: 83%
“…Furthermore, conflicting results were reported about OA effects on sea star growth rate, which can serve as a possible indirect indicator of skeleton stability (Table S1). At comparable level and duration of exposure, some studies reported a significantly decreased growth rate in A. rubens (Appelhans et al, 2012(Appelhans et al, , 2014Hu et al, 2018;Keppel et al, 2015) while others measured no significant effect or an increased growth rate in Pisaster ochraceus, Acanthaster planci or Luidia clathrata (Gooding et al, 2009;Kamya et al, 2017;Kamya et al, 2016;Schram et al, 2011). The same individuals A. rubens used in the present study had significantly reduced growth and feeding rates at low pH T-SW (7.4 and 7.2) after 85 and 105 days of exposure (Hu et al, 2018).…”
Section: Introductionsupporting
confidence: 49%
“…At comparable level and duration of exposure, some studies reported a significantly decreased growth rate in A. rubens (Appelhans et al, 2012(Appelhans et al, , 2014Hu et al, 2018;Keppel et al, 2015) while others measured no significant effect or an increased growth rate in Pisaster ochraceus, Acanthaster planci or Luidia clathrata (Gooding et al, 2009;Kamya et al, 2017;Kamya et al, 2016;Schram et al, 2011). The same individuals A. rubens used in the present study had significantly reduced growth and feeding rates at low pH T-SW (7.4 and 7.2) after 85 and 105 days of exposure (Hu et al, 2018). This suggests that, at these low pH, either the skeleton of the sea stars could be affected by OA or that the skeleton properties could be maintained at the expense of growth.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, our results contribute to an increasing body of research (Hu et al, 2018; that show the need to consider the influence of acclimation in assessing prospects for phenotypic adjustment and adaptation in marine species in the face of a changing climate.…”
Section: Discussionmentioning
confidence: 73%
“…This reduction of metabolic rate would be expected to impair the ability to persist in the face of habitat warming and acidification. Energetic responses to acidification conditions are also evident in long term studies of H. erythrogramma, other sea urchins and other marine invertebrates reared in acidification conditions, a result attributed to energetic constraints as seen in their smaller size, reduced biomineral production and lower gonad production/fecundity (Mos et al, 2016;Hu et al, 2018;Byrne and Fitzer, 2019;Johnson et al, 2020).…”
Section: Discussionmentioning
confidence: 92%